ANIMASI DENGAN GAMBAR BERGERAK MENINGKATKAN DAYA TARIK PROGRAM PROMOSI - Dewi Immaniar Desrianti; Ahmad Nur Firdaus; Deny Pangestu Gunawan (Universitas Raharja, 2017)
The development of creative industries is growing, as evidenced by the many industry-emerging creative industry. The media campaign is currently very helpful in supporting the information and communication All of that is because of the many interests of the creative industry services. Many competitors require companies to do promotions to attract customers. Penyajiaan media ads interesting and entertaining will encourage the general public to find out more detail and have an interest to join a company or institute of technology is so rapid in PT.Movio Screen as a company engaged in the creative industry. Have a good portfolio will make promotion and enhance the corporate image. 3D animation movie series is a very good portfolio and attractive for media promotion for a company in the field of creative industries, in addition to the 3D animated film can enhance a company's image. In the 3D animation movie of the series can also be a support to increase the creation of the nation of the 3D animated film, to be more creative again in making animated films in 3D and can inspire people to work in the creative industries in order to generate industry local animation, based on a story in this animation.